SINERGITAS PERAN PENTA HELIXDALAM PERUMUSAN STRATEGI PENGEMBANGAN UNIT USAHA WISATA - Titi Rahayu Prasetiani; Mahirun Mahirun; Andi Kushermanto; Tsamara Tsamara; Arya Ajhie (Jurnal Ekonomi dan Bisnis, 2023)
Pekalongan Regency as an autonomous region has superior potentials in various sectors, one of which is in the tourism sector. Tourism is one of the strategic development sectors that has a multiplier effect, both directly and indirectly, so that it has an impact on the social, cultural, educational and economic sectors of the country. Natural tourism potential owned by Pekalongan Regency is natural resources; mountains and sea.Sumurjomblangbogo Village as a strategic partner of the Faculty of Economics and Business, University of Pekalongan has the potential for a Tourism Business Unit from BUMDes Tirta Arum in the form of a swimming pool tourist attraction. The purpose of this study was to determine the function and role of each Penta Helix party in developing the superior tourism potential of the Tirta Arum swimming pool in Sumurjomblangbogo Village, Bojong District, Pekalongan Regency, as well as formulating a strategy for developing resource-based tourism superior potential (Resource Based View).The results of the study show that the synergy between Academicians (Academicians) Business (Business Doers), Government (Government), Community (Community) and Media in this village has conceptually been realized. Business actors play a role as the main actor in achieving sustainable profit. The government acts as a regulator and dynamicator to drive the local economy. While the media as a means of publication in promoting swimming pool attractions and building a brand image.